Modus Dominasi Pada Habitus Masyarakat Nadoman - Muhammad Zainal Arifin (PANTUN, 2019)
The forming of habitus is influenced by the dominance modus of an agent who is successful on applying his capital in a field. The capital meant by Bourdieu in a habitus theory are economic capital, cultural capital, social capital, and symbolic capital. The modus of dominance can be seen through the application of one’s symbolic capital. The higher one’s symbolic capital, the more powerful he is to control his surroundings. The capitals are from pride and prestige possessed. The habitus of Nadoman people on the Mosque Council of Tsamrotul Fuad Islamic Boarding School Cipasung is constructed based on the dominance modus conducted by the people with their symbolic power. The method of this research is qualitative by applying Pierre Bourdieu’s habitus theory. The result shows that Nadoman people behave based on the dominance of an agent’s symbolic power within their relation concept guiding individuals to adapt in their conflicting situation.Keywords: habitus, dominance, Nadoman, behavior, Pesantren/Islamic boarding school